The Effectiveness of Non-Formal Physical Education Curriculum for the Physical Development of 11-13-Year-Old Children - Asta Šarkauskienė; Antanas Lukoševičius; Bronė Švitrienė (Lithuanian Sports University, 2018)
Background. This  study  aims  to  develop  and  implement  a  curriculum  of  non-formal  physical  education  in school and assess its effectiveness for the physical development of 11−13-year-old children. Methods. The research was conducted in two stages. In the first stage 51 fifth grade children (M age  = 11.3 years) participated in a quasi-experiment for two years. The children were organized into two groups: E and C. Both groups shared the duration (1 hour) and frequency (twice a week) but were different in their education curriculum. In the second stage (after four years) 72 sixth graders (M age  = 13.0) participated from the same comprehensive schools. The focus groups underwent anthropometric (height, weight, BMI) and physiometric (VC, right and left handgrip strength) measurements. Dependent t test indicated that over two years E and C group girls' and boys' height, weight, right and left handgrip strength indices increased significantly, p < .05. Results. E group girls' and boys' BMI and C group girls' VC indices did not change significantly, p > .05. Independent  t  test  indicated  that  in  the  second  research  stage  differences  in  anthropometric  and  physiometric measurements of groups were not significant, p > .05. Conclusion. The developed and implemented curriculum of non-formal education in the schools had the biggest positive effect on the decrease of 11−13-year-old children's levels of BMI and the increase in the VC levels. Keywords:  11−13-year-old children, non-formal physical education, physical development.